2022
DOI: 10.3389/fmars.2021.790869
|View full text |Cite
|
Sign up to set email alerts
|

Bioconstruction and Bioerosion in the Northern Adriatic Coralligenous Reefs Quantified by X-Ray Computed Tomography

Abstract: The northern Adriatic continental shelf hosts several coralligenous reefs rising from the sedimentary bottom and characterized by three main benthic assemblages, respectively, dominated by algal turfs, encrusting calcareous rhodophyte (ECRs) or erect sponges. Bioconstruction and bioerosion processes have been investigated using recruitment travertine limestone tiles deployed in a random site for each main benthic assemblages off Chioggia, 6.1–14.4 km offshore and 20.2–25.4 m depth. Tiles were retrieved after 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…On the other hand, the monitoring of the nuclei provided information on fast-growing species that rapidly colonized both the nuclei and the pipeline concrete coating after one year of immersion (i.e., encrusting corallinales, encrusting sponges, Reteporella sp., and serpulids). These taxa have been reported as opportunistic or characteristic of the first stage of community development on coralligenous reefs (Fava et al, 2016;Sartoretto et al, 2017;Casoli et al, 2020b;Turicchia et al, 2021). Albeit not analyzed in the present work, fast-growing species settled on the pipeline sections not interested by nuclei relocation, so we can argue that their settlement was not influenced by the relocation activities.…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, the monitoring of the nuclei provided information on fast-growing species that rapidly colonized both the nuclei and the pipeline concrete coating after one year of immersion (i.e., encrusting corallinales, encrusting sponges, Reteporella sp., and serpulids). These taxa have been reported as opportunistic or characteristic of the first stage of community development on coralligenous reefs (Fava et al, 2016;Sartoretto et al, 2017;Casoli et al, 2020b;Turicchia et al, 2021). Albeit not analyzed in the present work, fast-growing species settled on the pipeline sections not interested by nuclei relocation, so we can argue that their settlement was not influenced by the relocation activities.…”
Section: Discussionmentioning
confidence: 59%
“…This new carbonate deposit represents a suitable material used as growth substrate for bioeroders (Spencer and Viles, 2002). Carbonate accretion and bioerosion rate affect the habitat structure of both tropical coral reefs (Hutchings, 1986) and coralligenous reefs in the Mediterranean Sea (Turicchia et al, 2022), with remarkable effects on biodiversity and biogeochemical cycling. Bioerosion acts over a wide range of natural substrates, such as encrusting coralline algal thalli and calcareous skeletons of living and dead organisms (Le Tribollet and Payri, 2001;Hutchings and Peyrot-Clausade, 2002;Bick, 2006;Smith et al, 2015;Meyer et al, 2021;Ramıŕez-Viaña et al, 2021).…”
Section: Bioerosion: Essential Bibliographic Reviewmentioning
confidence: 99%
“…The change in boring behaviour of some species during their growth, the wide range of factors influencing it, and the similar erosive patterns produced by different species make it difficult to attribute a boring pattern to a single species. Throughout the literature, many Entobia have been attributed to different species of clionaids considering the morphological characteristics of the cavities [17]; an example is Entobia cateniformis, ichnospecies firstly attributed to Cliona vermifera (Hancock, 1867) by Bromley and D'Alessandro [17], while Färber et al [13] assigned it to Cliona schmidtii (Ridley, 1881), and more recently, Turicchia et al [27] attributed it to Cliona viridis. Conversely, our results in this study suggested E. cateniformis as a possible trace marker for D. pulchella mediterranea.…”
Section: General Remarksmentioning
confidence: 99%